Optimasi Perencanaan Penggantian Pegas Daun pada Truk Hino FM 260 Jd di PT PP Presisi Tbk Proyek Tol Indrapura–Kisaran - Praditya, Ardhi Nur Praditya; Winarto, Felixtianus Eko Wismo (Jurnal Teknologi dan Rekayasa Alat Berat, 2024)
Leaf springs are an important component of a truck's suspension system, but they can suffer premature failure due to extreme road conditions and inadequate maintenance implementation. This can disrupt construction projects and lead to increased costs. A study was conducted to investigate the factors that cause leaf spring failure on the Hino FM 260 JD unit in the Indrapura–Kisaran toll road construction project, North Sumatra. This study found that the average life of front leaf spring components is shorter than the manufacturer's recommended service life. This was caused by the extreme road conditions in the region, as well as inadequate implementation of maintenance by the project team. Adopting new replacement recommendations will result in reduced component efficiency and increased prices. The findings of this study emphasize the importance of proper maintenance and replacement of leaf springs to prevent disruptions in construction projects. This study also provides insight into the factors that can cause premature leaf spring failure, which can be used to improve the reliability of truck suspension systems. The results of the analysis provide recommendations for planning the replacement of one type of spring with a range of 46,011.62 to 51,959.58 kilometers.